Evaluation of Clinical Course Assessment of Medical Students in Virtual Education - Narjes Moharami; Mahsa Shakour (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: One of the important daunting challenges preseted to  clinical education is the process of students’ evaluation, which is debatable holding virtual education and the accurate assessment of this process improves clinical evaluation. The present study aimed aim of this study was to assesse the virtual evaluation process of clinical medical students during COVID-19 pandemic. Methods: This meta-evaluation study was conducted to assess the evaluation process of students using Kirkpatrick's model level 1& 2. A total of 120 clinical medical students were selected from among the students of Arak hospitals by simple random sampling in 2021. The data collection tools incluyded two researcher-made questionnaires (questionnaire related to face-to-face and non-face-to-face evaluation). The validity of the checklist was confirmed by faculty members of Arak University of Medical Sciences with the help of content validity index and content validity ratio. Data were analysed using SPSS software (version 16). In order to compare the variables between the studied populations, by establishing the assumption of normality, parametric tests, such as analysis of variance and independent t, were used. A significance level of .5 was considered. Results: Comparing the mean scores of three groups of internal medicine trainees before COVID-19 pandemic and two groups during the pandemic demostrated that themean scores decreased significantly during COVID-19 (P=0.02). In the virtual evaluation, students answered the whole 14 questions. 78.8% of students assessed this evaluation method as very unfair. A large percentage of students (63.7) did not consider the score they obtained as an expression of their clinical ability. According to the opinion of the majority, it was very easy to access the site; nonetheles, the results were presented with a delay. In the face-to-face evaluation, students answered seven questions. A large percentage of students did not consider the questions to be in accordance with the education. Both methods had negligible effects on improving motivation and the students believed that they would have gotten a better grade if they used the other method. Conclusion: The face-to-face and virtual evaluation of clinical students had defects, such as problems with the system and grading, inability to motivate  and the assessment of clinical ability and incompatibility of questions with education, requiring further investigations and finding interactive and combined methods.